Perfect passage - Merkies, K.; Sheiner, J.; Tiidus, M. (Embracing science to enhance equine welfare and horse-human interactions, 2013)
Passage is a complex movement described as a "measured, very collected, elevated and cadenced trot...characterized by a pronounced engagement of the hindquarters, a more accentuated flexion of the knees and hocks, and the graceful elasticity of the movement. Each diagonal pair of legs is raised and returned to the ground alternately. In principle, the height of the toe of the raised forefoot should be level with the middle of the cannon bone of the supporting foreleg. The toe of the raised hind foot should be slightly above the fetlock joint of the supporting hind leg."1 This perfect ideal of passage presents a training and physiological challenge for the horse that may not be achievable. Five still frames of passage from each of three dressage tests performed by five horse-rider pairs during the 2010 World Equestrian games were observed. The height of the raised fore and hind foot in comparison to the contralateral leg were classified as below, equal to, or above the "FEI-ideal" positioning for that leg. Of the 74 still frames observed, there was a large variation in the quality of the steps, however the ideal passage was observed most frequently (27%). When considering only the front legs, 39.2% of the steps were above ideal, with the majority of these steps (66%) paired with hind leg elevation below ideal. No horse demonstrated a passage with both front and hind legs below ideal. Horses were inconsistent in their performance of passage, alternating between at least two, and generally three classifications (fore/hind legs high/at/below ideal) of leg elevation. Layperson`s paragraph: Passage is a difficult and important movement in Grand Prix dressage. Horses in competition more often perform passage with front leg elevation higher than required by the FEI rules accompanied by below-ideal hind leg elevation. Competitions are judged subjectively and riders may receive higher scores for flashier movements, which leads to inconsistency in the sport.